PENGARUH LITERASI BACA TULIS TERHADAP CAPAIAN KOMPETENSI BERBAHASA SISWA KELAS I SD - Tawurutubun, Elisabeth; Tur Rosidah, Cholifah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This research is motivated by the importance of literacy in improving the language skills of grade I elementary school students. As a basic skill, literacy plays a role in supporting the overall mastery of language aspects. This study aims to examine the extent to which literacy affects the achievement of language competence of grade I elementary school students. The population used in the study was 40 students of SDN Dr. Soetomo V Surabaya who were in classes 1A and 1B The method used was quasi-experiment with a pretest-posttest design in a quantitative approach. Data were obtained through language proficiency tests that included aspects of reading and writing. Students are given a pretest to find out their initial ability, then a posttest after participating in a literacy program to measure their improvement. Data analysis was carried out by comparing the results of the pretest and posttest to see the impact of literacy on the development of students' language competence. The results of the study show that the literacy program has a positive impact on students' language skills. Of the 40 students involved, 22 students (55%) experienced a significant increase in scores after participating in the literacy program. However, statistical analysis showed that there was no significant difference between classes 1A and 1B (p-value 0.653). These findings suggest that literacy can improve students' language skills, although there was no significant difference between the experimental and control groups.